Oral cancer mortality trends in Brazilian geographical regions from 1996-2001. - L.C.M. Loffredo; C. Pinelli; T.R.C. Vitussi; M.L.M.M. Sundefeld; J.A.D.B. Campos (São Paulo State University (UNESP), 2006)
The purpose of this study was to analyse the oral cancer mortality trends in Brazil by geographic region, age and sex, from 1996 to 2001. The Brazilian Ministry of Health database DATASUS and the Brazilian Institute of Geography and Statistics were used as the source of data. Oral cancer mortality rates per 100,000 population were estimated. Statistical analyses comprised estimates of oral cancer mortality rates, grouped according to the study variables, in 1996, 1997, 1998, 1999, 2000 and 2001; also, the three-year periods 1996-1998 and 1999-2001 were analysed, allowing the oral cancer mortality trends between these two periods to be calculated. For comparison, in each geographical region, the ratio between two death rates (related to period or sex) was calculated. In the period 1996-2001, a total of 25,972 deaths due to oral cancer were reported, giving a mortality rate of 2.67. The rates for the periods 1996- 1998 and 1999-2001 were 2.53 and 2.73, respectively, showing a slight increase in the rate. There was a predominance of oral cancer in males with a male/female ratio of approximately 4. All regions exhibited an increase in mortality rates, with the exception of the Southeast region. From 1996 to 2001, the average mortality rates were 3.55 and 3.58 for the Southeast and South regions, and 1.94, 1.41, and 0.86 for the Mid-West, Northeast, and North regions, respectively. Over the age of 40, oral cancer mortality rates were seen to increase rapidly with age. Oral cancer mortality increased in all regions, except in the Southeast, and was considerably higher among males and older individuals.